VUCA World and Environmental Law - Chauhan , Richa; Rani, Rishika; Pranali (International Journal of Psychosocial Rehabilitation, 2020)
Volatility, Uncertainty, Complexity, and Ambiguity: The acronym VUCA has come to define the digital and current economy as a highly unpredictable environment and potentially corrective to incremental focus. The term VUCA was initially given by the US WAR College to define circumstances faced by military personnel. In recent times the notion has come to describe the competitive environment of the digital market (Benett & Lemoine, 2014) in which organizations must adapt past structures to match environmental changes (Heugens & Landes, 2009). Businesses operate in an environment that is volatile, unpredictable, uncertain, and accelerated. VUCA is fast becoming a catchphrase in the corporate arena and in the physical environment and law, and it is an often-discussed topic for today’s adoptive leaders during annual strategy, and the rapid rate of change in our business environment is throwing many organizations and their leaders pretty much off balance as they are unable to keep pace with the vagaries of the VUCA world. This paper is an attempt to understand how VUCA practices can be used in environmental law.